A Feminist Analysis of Shadow Powers, the State, and Citizen Responses: The Case of Contemporary Mexico. (June 2015) - Carlsen, Laura E.
<x xml:space="preserve">Abstract</x> Throughout Latin America, the nature and location of power have shifted rapidly, in large part due to the emergence of new "shadow powers." These power groups act beyond institutional and legal frameworks and yet also interact with them. They operate clandestinely and yet openly control and rule in large swaths of national territory. Our capacity to adequately define them and their realms of activity is limited, and yet their effects on daily life can be huge. The model of the state fighting to eliminate the challenge posed by these powers is inadequate, as we see increasing alliances between elements of the state and shadow powers. Applying a feminist analysis of power, this article explores these contradictions in the case of Mexico, where a volatile mix of organized crime, government corruption, and legal and illegal economic interests have changed the map of power and led to conflicts. It focuses on the new dynamics of power and citizen responses to resist the imposition of illegitimate power and eliminate all forms of violence, with an emphasis on violence against women, which rises considerably in the context of shadow powers.